PERTANGGUNGJAWABAN PENYIDIK KEPOLISIAN REPUBLIK INDONESIA DAN UPAYA HUKUM YANG DILAKUKAN OLEH TERSANGKA DALAM HAL TERJADINYA ERROR IN PERSONA (STUDI KASUS REZA FAHLEFI) - Reza Adilla; Erdianto '; Ledy Diana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
It is important in a constitutional state is their appreciation and commitment to uphold human rights and guarantee all citizens are equal before the law in (equality before the law). Thus ideally principle is not just contained in the Act of 1945 and legislation. But it is more important and foremost is the implementation in its implementation.Pekanbaru Police Investigator accountability In This occurrence Error In Persona Based Case Studies Reza Fahlefi, Regarding criminal responsibility Pompe mention toerekenbaarheid elements, covering a willingness to think the act that allows the manufacturer to master his mind and determine his will, and therefore the manufacturer can understand the meaning and effect of his actions, and by sabab that, the manufacturer determines his will to his opinion (about the meaning and consequences). that the criminal act is at the center of his actions, the responsibility opposite the center is the person doing the act but the act of criminal liability in criminal law, there is a close relationship, as well as actions by people who do act, new criminal acts have meaning if beside there is accountability, otherwise there is no accountability if there is no criminal liability. The error is an element, even a necessary condition for the existence of which include the imposition of criminal liability. Keywords: Criminal Liability